CORPORATE GOVERNANCE, FIRMS’ PROFITABILITY AND SUSTAINABILITY IN RURAL COMMUNITY BANKS: EVIDENCE FROM GHANA . - Eric Nsiah Gyabaah, Emmanuel Opoku Marfo, Kofi Owiredu-Ghorman & Kwame Oduro Amoako (International Journal of Research Science and Management, 2018)
The paper examines the relationship between Corporate Governance mechanisms (compliance to sound corporate governance practices, board size, board members’ educational qualifications and bank’s reputation),and profitability and sustainability of Rural Community Banks (RCBs) in Ghana. Data was obtained from key stakeholders of the nineselected RCBs using questionnaire. The results of this study indicate that corporate governance mechanisms especially, board size, regulatory compliance and bank’s reputation have a significant effect on the RCBs profitability and sustainability. Nevertheless,board member’s educational qualifications was insignificantly related to profitability and sustainability of the RCBs.In this regard, the study recommendsthe strengthening of corporate governance by appointing competent Board of Directors and management forRCBs to improve on theirprofitability and sustainability. In addition, providing appropriate training for staff, improving the conditions of service and ensuring effective monitoring and supervision by supervisory agencies are key to the profitability and sustainability of RCBs in Ghana.